Blood-brain barrier integrity is the primary target of alcohol abuse. (1st March 2021) - Wei, Jiangping; Dai, Yuan; Wen, Wen; Li, Jin; Ye, Lingyu Linda; Xu, Shijun; Duan, Dayue Darrel
Abstract: The effects of long-term alcohol consumptions on cognitive function remain elusive with contradictory results. Whilst it is widely accepted that long-term intoxication can cause cognitive impairment, moderate drinking can improve cognitive function. In reality, many older people and those with chronic medical conditions are long-term alcohol consumers in Asian countries. Our previous studies have suggested that long-term alcohol consumption can damage blood-brain barrier (BBB) integrity and aggravate cognitive deficit in APPswe/PS1De9 mice, but little is known about the underlying mechanisms, especially whether this consumption can cause cognitive decline via aggravating BBB damage in people who are exposed to the risk factors for cognitive disorders such as aging or inflammation. These questions were addressed in this study. The mouse models of cognitive deficit induced by d -galactose or lipopolysaccharide, the important risk conditions in human on cognitive function, were used to evaluate the effects of long-term alcohol consumption on the BBB integrity. After alcohol administration for 30 days in these models the BBB integrity was significantly destroyed with remarkably increased permeability and down-regulated protein expression of zonula occludens-1, VE-cadherin, occludin, low-density lipoprotein receptor-related protein-1, receptor for advanced glycation end products, major facilitator superfamily domain-containing protein-2a and aquaporin-4, which is the most closely related with the structure and function of BBB integrity. Meanwhile, the level of oxidative stress in d -galactose mice or inflammatory factors in cortex and serum in lipopolysaccharide mice, which might be involved in the cognitive dysfunctions, was significantly amplified. Furthermore, the impaired memory and hippocampal neuron damage induced by d -galactose and lipopolysaccharide were concurrently aggravated. Collectively, our study provided novel and compelling evidence that the structural and functional proteins for BBB integrity may be the primary targets for the detrimental effects of alcohol abuse that lead to cognitive dysfunction and neurological deficits in high risk populations. Graphical abstract: A detailed illustration of the experiment. Image 1 Highlights: Alcohol consumption aggravates the BBB permeability changes and cognitive declince. Alcohol consumption destroys the BBB integrity by regulating the expression of the structural and functional proteins. Alcohol consumption aggravates the level of oxidative stress or inflammation in brain.